EFEKTIVITAS MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) TERHADAP KEMAMPUAN PEMAHAMAN KONSEP DAN PEMECAHAN MASALAH PADA MATERI GEOMETRI DERAJAT DAN RADIAN DI KELAS X SMA NEGERI 2 DOLOK SANGGUL TP. 2019/2020 - Siregar, Enita Octalia (Jurnal Visi Eksakta, 2025)
This research is a quasi experimental research. This study aims to see if there is an effect of Think Pair Share Learning Model on concept understanding and problem solving skills. The population in this study were all X grade students of SMA Negeri 2 Doloksanggul, which amounted to 6 classes in the 2019/2020 school year. In this study, the independent variable ( ) is the TPS learning model on degree and radian material. the coefficient of determination from the calculation results = 61.2%. Based on the results of the calculation of the correlation coefficient significance test, it is obtained thitung > ttabel or 0.779> 0.349 which means that there is a strong relationship between the Think Pair Share learning model on the ability to understand concepts and problem solving obtained thitung > ttabel or 0.782> 0.349 which means that there is a strong relationship between the Think Pair Share learning model on problem solving. From the results of this discussion, the hypothesis in this study is accepted, namely “There is an Effect of the Think Pair Share Learning Model on the Ability of Concept Understanding and Problem Solving on Geometry Material Degrees and Radians in Class X SMA Negeri 2 Doloksanggul T.P. 2019/2020”.